The evolution of guidelines for the validation of flow cytometric methods. (14th May 2015) - Du, L.; Grover, A.; Ramanan, S.; Litwin, V.
Summary: The recent advances in the field of flow cytometry have resulted in instrumentation with increased capacity which is actually more user‐friendly. Thus, the technology has become more valuable to research scientists, the pharmaceutical industry and clinical laboratories. The use of flow cytometry in regulated labs has been hampered by the challenges associated method validation and the lack of official guidance documents on the topic. Thus key stakeholders have published recommendation papers with the hope that these will be incorporated as official guidance documents. This review will focus on the achievements of the stakeholders and a high‐level overview their recommendations.